Cluster sustainability in peripheral regions: A case study on Israel's and Finland's biotechnology industries - Shiri M. Breznitz; Antti-Jussi Tahvanainen (The Research Institute of the Finnish Economy (ETLA), 2010)
Even with globalization, industrial clusters are maintaining their importance in today's economy. With the decomposition of production we find that clusters are becoming focused on specific industries and stages of production. This paper analyzes two peripheral Western countries, Finland and Israel, which saw success in their ICT clusters and wanted to duplicate this success building on their knowledge in the life science industry to create biotechnology clusters. This paper focuses on two innovation-based clusters, the biotechnology agglomerations in Rehovot, Israel, and Helsinki, Finland. These industrial districts consist of companies, many spun out of university research, that are either devoted to earlystage R&D (Israel), or choose to conduct the entire business cycle (Finland). Utilizing a multimethod study that includes both quantitative and qualitative research, with a series of indepth interviews and site visits, archival and statistical data, the paper investigates whether a cluster of young research companies can become the basis of industrial growth and bring economic sustainability to a region. We find that while the firms' strategic choices regarding their focus on certain positions in the value chain do not necessarily have any direct implications on the sustainability of the respective clusters as such, a variety of other characteristics necessary for long-term sustainability are missing in both clusters. These include particularly inter-firm knowledge flows within the clusters, an active and demanding VC market, connections to international expertise, and opportunities to recruit experienced expertise.
Keywords: 330; Clusters; Biotechnology; Peripheral Regions; Sustainability; Biotechnische Industrie; Regionale Konzentration; Arbeitsteilung; Strategische Unternehmensplanung; Finnland; Israel